2016
DOI: 10.1111/bjet.12457
|View full text |Cite
|
Sign up to set email alerts
|

Interactions and learning outcomes in online language courses

Abstract: Interactions are the central emphasis in language learning. An increasing number of K-12 students take courses online, leading some critics to comment that reduced opportunities for interaction may affect learning outcomes. This study examined the relationship between online interactions and learning outcomes for 466 students who were taking high-school level online language courses in a Midwestern virtual school. Regression analysis was employed to examine how three broad types of interactions, learner-instru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
51
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 76 publications
(60 citation statements)
references
References 43 publications
5
51
1
3
Order By: Relevance
“…Inversely, research has found that developing student-teacher relationships improved teachers' job satisfaction at a full-time online high school (Borup & Stevens, 2016a;Drysdale, Graham, & Borup, 2016). Furthermore, Lin, Zhang, and Zheng's (2017) analysis of 466 online students' survey responses at a virtual high school found that learner-instructor interactions had a positive relationship with student satisfaction. While not generally the case with the students who participated in our research, previous research at full-time online high schools has found that online teachers were successful in forming close relationships with students through regular, sustained online communication.…”
Section: Discussionmentioning
confidence: 99%
“…Inversely, research has found that developing student-teacher relationships improved teachers' job satisfaction at a full-time online high school (Borup & Stevens, 2016a;Drysdale, Graham, & Borup, 2016). Furthermore, Lin, Zhang, and Zheng's (2017) analysis of 466 online students' survey responses at a virtual high school found that learner-instructor interactions had a positive relationship with student satisfaction. While not generally the case with the students who participated in our research, previous research at full-time online high schools has found that online teachers were successful in forming close relationships with students through regular, sustained online communication.…”
Section: Discussionmentioning
confidence: 99%
“…Students with the high‐quantity profile reported the highest satisfaction, followed by those with the good quality profile, though these two profiles did not differ from each other significantly in post hoc analysis. Unlike previous online learning studies that either found intrinsic and extrinsic motivation had no power to predict satisfaction (Lin et al , ), or there was no significant correlation between motivation (using RAI) and satisfaction (Chen & Jang, ), our study’s person‐centered approach allowed us to endorse multiple motivational types simultaneously. We believe that it is only from such a simultaneous and inclusive inspection, and not from a variable‐centered approach that assumes linear relationships and homogeneous populations, that we can understand the subtle and complex relationships among motivations and online learning satisfaction that exist in real individuals' day‐to‐day lives.…”
Section: Discussionmentioning
confidence: 71%
“…Satisfaction has a close, inverse relation to online learning dropout rates (Kuo, Walker, Schroder, & Belland, 2014) and reflects cognitive achievements in online learning (Palmer & Holt, 2009;Puzziferro, 2008). It ranks alongside achievement (ie, final scores) and perceived learning as a key indicator of online learning outcomes (Chen & Jang, 2010;Lin, Zheng, & Zhang, 2017). Chen and Jang (2010) reported that self-reported motivation had no predictive power over satisfaction.…”
Section: Motivational Profiles and Learning Outcomesmentioning
confidence: 99%
“…Despite this fact, a large number of individual studies showed the positive learning outcomes of online learning strategies [12][13][14][15][16].…”
Section: Outcome and Analysismentioning
confidence: 99%